Comparison of Improvement of Quality of Life After Using Ready- Made Spectacles and Custom-Made Spectacles in Junior High School Students in Bandung District - Dianita Ginting; Susanti Natalya; Rova Virgana; Aldiana Halim (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Introduction: Uncorrected refractive error remains a leading cause of blindness and visual impairment among different population groups worldwide. In school children, it has a considerable impact on quality of life including social development, school performance and academic achievement that can affect their future. Management of refractive errors in developing countries is not adequate related to the cost, availability and distance of health and optical services. Hence, early detection and intervention with ready-made spectacles at the time of school children vision screening programs is expected to help solving these problems. Objective: To evaluate outcome measure of wearing ready-made spectacles (RMS) and custom-made spectacles (CS) on children’s quality of life.Method: A non-inferiority trial with a margin of 25%, cluster-randomized trial. Children aged 11-15 years in Bandung Regency, that meet the inclusion criteria were randomized to receive RMS and CS. Main study outcome was global score on the National Eye Institute Refractive Error Quality of Life- 42 after one month of wearing study glasses, comparing both group. Result: A total of 220 eligible subject were allocated to RMS (n = 110) and CS groups (n = 110) respectively. Baseline and end line score data were available for 220 (100%) of subjects. Improvement of quality of life in RMS group was 19.48±9.33 and CS was 24.14±9.68 with D = -18.11(CI 95% - 19.36 to -16.64). Conclusion: Improvement of quality of life in RMS group is non-inferior compare with CS group